The genus Bolbonema Cobb, 1920 (Nematoda: Desmodoridae): emended diagnosis, key to males, and description of three new species from the continental shelf off northeastern Brazil - Larrazábal-Filho, Alexandre L.; Neres, Patrícia F.; Esteves, André M. (Zootaxa, 2018)
The marine nematode genus Bolbonema has three valid species, the most recent one described eight years ago. Characteristics of the genus include the well-defined globular cephalic capsule and the long and short somatic setae along the body. Three previously undescribed species of this genus were collected on the continental shelf of the Potiguar Basin in northeastern Brazil. Bolbonema braziliensis sp. n. has a relatively large cryptospiral fovea amphidialis, gubernaculum a bent rod dorsally oriented and two subventral precloacal setae inserted on two small papillae above the cloaca. Bolbonema papillae sp. n. has a large multispiral fovea amphidialis with three turns, arched spicules with the proximal region rounded, a laminar and well-developed gubernaculum enfolding the distal portion of the spicules, and two subventral precloacal papillae just above the cloaca. Bolbonema zildae sp. n. has a spiral fovea amphidialis, no supplements, arched spicules with a velum, and the gubernaculum with a dorsal apophysis. These three new species increase to six the number of taxa known in the genus. A dichotomous key based on males, an emended diagnosis of the genus, and the first record of Bolbonema brevicolle Cobb, 1920 from Brazil are provided.